Optimum multiple tuned mass dampers for structures under the ground acceleration based on the uniform distribution of system parameters. - Li, Chunxiang (Earthquake engineering & structural dynamics.)
The five MTMD models, with natural frequencies being uniformly distributed around their mean frequency, have been recently presented by the first author. They are shown to have the near zero optimum average, damping ratio (more precisely, for a given mass ratio there is an upper limit on the total number, beyond which the near zero optimum average damping ratio occurs). In this paper, the eight new MTMD models (i.e. the UM-MTMD1~UM-MTMD3, US-MTMD1~US-MTMD3, UD-MTMD1 and UD-MTMD2), with the system parameters (mass, stiffness and damping coefficient) being, respectively, uniformly distributed around their average values, have been, for the first time here, proposed to seek for the MTMD models without the near zero optimum average damping ratio. The structure is represented by the mode generalized system corresponding to the specific vibration mode that needs to be controlled. Through minimization of the minimum values of the maximum dynamic magnification factors (DMF) of the structure with the eight MTMD models are investigated to evaluate and compare their control performance. The optimum parameters include the optimum mass spacing, stiffness spacing, damping coefficient spacing, frequency spacing, average damping ratio and tuning frequency ratio. The six MTMD models without the near zero optimum average damping ratio (i.e. the UM-MTMD1~UM-MTMD3, US-MTMD1, US-MTMD2 and UD-MTMD2) are found through extensive numerical analyses. Likewise, the optimum UM-MTMD3 offers the higher effectiveness and robustness and requires the smaller damping with respect to the rest of the MTMD models in reducing the responses of structures subjected to earthquakes. Additionally, it is interesting to note, by comparing the optimum UM-MTMD3 with the optimum MTMD-1 recently investigated by the first author, that the effectiveness and robustness for the optimum UM-MTMD3 is almost identical to that for the optimum MTMD-1 (without inclusion of the optimum MTMD-1 with the near zero optimum average damping ratio). Recognizing these performance benefits, it is preferable to employ the optimum UM-MTMD3 or the optimum MTMD-1 without the near zero optimum average damping ratio, when installing the MTMD for the suppression of undesirable oscillations of structures under earthquakes.